3x=2(7x-3)

Simple and best practice solution for 3x=2(7x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x=2(7x-3) equation:


Simplifying
3x = 2(7x + -3)

Reorder the terms:
3x = 2(-3 + 7x)
3x = (-3 * 2 + 7x * 2)
3x = (-6 + 14x)

Solving
3x = -6 + 14x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14x' to each side of the equation.
3x + -14x = -6 + 14x + -14x

Combine like terms: 3x + -14x = -11x
-11x = -6 + 14x + -14x

Combine like terms: 14x + -14x = 0
-11x = -6 + 0
-11x = -6

Divide each side by '-11'.
x = 0.5454545455

Simplifying
x = 0.5454545455

See similar equations:

| 80+5x=7x | | 4(5r-5)=-20-7r | | -5=7-2x | | (3x-1)(x+2)=-1 | | -x-3(-5x-8)=136 | | (12^5)/(9^2)*(4^4) | | 12^5/9^2*4^4 | | 0.3x-2(0.1x+0.4)= | | (3a-9)/(3a-6)*(a/a^2-9) | | {(3a-9)/(3a-6)}*(a/a^2-9) | | f(x)=-3.25(-4.2) | | 18=2v+4 | | 6+2(5x-1)=84 | | 18-12a= | | 108=-6(3+3x) | | 5h-3h+9h= | | 42n-12=0 | | Log(7)25=2log(7) | | 3a-9/3a-6*a/a^2-9 | | 7(4+h)=13h | | sin(2x-60)=-cos(3x) | | 121=-11b | | 5p-7=2p | | 90-x=0.8(x) | | 1/2d-12 | | 83=-3(6b+3)+2 | | x^2+y^2+8y=9 | | 40-10x=40+2x | | 11x+12=265 | | 2m-3n=1 | | 33=-5-2x | | (2x-5)=(45) |

Equations solver categories